MEMBANGUN BUDAYA ORGANISASI YANG INKLUSIF: TANTANGAN DAN KEUNTUNGAN DARI KEBIJAKAN DIVERSITAS - Arisanti, Nadia Prasista; Ahmadi, Mirzam Arqy (Cahaya Ilmu Bangsa, 2025)
In the context of organizations, diversity and inclusion become important issues that must be managed to improve employee performance and satisfaction. Diversity can influence the mindset and values of each individual, thus requiring effective policies to manage differences that can build an inclusive organizational culture. This research aims to analyze the relationship between diversity and inclusion policies and cultural effectiveness, identifying the challenges and benefits of implementing these policies. The method used is a literature review with a qualitative approach, collecting data from indexed scientific articles between the years 2018 to 2024. The implementation of diversity and inclusion policies has proven to enhance creativity, better decision-making, as well as employee engagement and retention. An inclusive work environment contributes to the productivity and reputation of the organization. The implementation of diversity and inclusion policies provides significant benefits to the organization, but challenges such as employee resistance and lack of management support need to be addressed to achieve optimal results. Diversity must be balanced with inclusion to create a productive organizational culture. Dalam konteks organisasi, keberagaman dan inklusi menjadi isu penting yang harus dikelola untuk meningkatkan kinerja dan kepuasan karyawan. Keberagaman dapat mempengaruhi pola pikir dan nilai setiap individu sehingga memerlukan kebijakan yang efektif untuk mengelola perbedaan yang dapat membangun budaya organisasi yang inklusif. Penelitian ini bertujuan untuk menganalisis hubungan antara kebijakan diversitas dan inklusi dengan efektivitas budaya, mengidentifikasi tantangan dan keuntungan dari implementasi kebijakan tersebut. Metode yang digunakan adalah literature review dengan pendekatan kualitatif, mengumpulkan data dari artikel ilmiah terindeks antara tahun 2018 hingga 2024. Penerapan kebijakan diversitas dan inklusi terbukti meningkatkan kreativitas, pengambilan keputusan yang lebih baik, serta keterlibatan dan retensi karyawan. Lingkungan kerja yang inklusif berkontribusi pada produktivitas dan reputasi organisasi. Implementasi kebijakan diversitas dan inklusi memberikan keuntungan signifikan bagi organisasi, namun tantangan seperti resistensi karyawan dan kurangnya dukungan manajemen perlu diatasi untuk mencapai hasil optimal. Keberagaman harus diimbangi dengan inklusi untuk menciptakan budaya organisasi yang produktif.